THE NEW PAYMENT SCHEME FOR ROMANIAN YOUNG FARMERS: EVOLUTION AND TERRITORIAL CHARACTERISTICS - Daniela Nicoleta BĂDAN (VOICILĂ); Gina FÎNTÎNERU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this study is to analyze the evolution of the volume of direct payments for young farmers from Pillar I of the Common Agricultural Policy (The Young Farmer Payment Scheme) in the period of 2015 to 2019, at national and European level. The study also analyze the links between the volume of the amount authorized for this support scheme and various socio-economic indicators of rural areas in Romania. The statistical data used in the study has been taken from the structured national bases at county level and analyzed using the correlation method. The results of this study is indicating that the support of the payment scheme has contributed to the growth of the share of young farmers numbers, with strong territorial differences. Determining the intensity of the relationship between the volumes of the amount authorized for the payment of young farmers through the first pillar and certain socio-economic variables of the rural environment may contribute to the explanation of certain regional patterns.